Financial Factors and Efficient Supply Chain Practices Affecting the Profitability of Vietnamese Commercial Banks - Pham, Duc Huy; Nguyen, Hong Anh Thi; Cao, Tan Huy (International Journal of Supply Chain Management, 2020)
This paper empirically analyses the factors that determine the profitability of Vietnamese commercial banks from 2010 to 2018 along with the efficiency of supply chain practices. Due to the balance sheet data of 26 commercial banks in Vietnam, we use regression models such as OLS, REM, FEM, and GMM to find the correlation between the factors with the profitability of the banks. We found that the differences between the regression models and results of Sargan-Hensen test and AR (2) test showed that the GMM estimation model was the best to analyze the factors affecting the profitability of commercial banks in Vietnam. We recognize a positive correlation between the bank's profitability during these years with equity-to-total assets, the ratio of customer deposits to total liabilities, the annual growth rate of customers’ deposits, diversification of income and efficiency of supply chain practices. The loans-to-total assets ratio, the ratio of loan loss provisions to net loans and the cost-to-income ratio will reduce the profitability of the bank as well as the non-economic of scale in the Vietnamese banking system. Finally, we found the macroeconomic factors giving an impact on the Vietnamese banking system.